Erector spinae plane block versus transversus abdominis plane block for analgesia after cesarean section: a systematic review and meta-analysis - Mariana AbdElSayed Mansour; Saeed Baradwan; Ahmed Abdelaziz Shama; Mohamed Ali Mahmoud; Ayman Salah Abouelnour; Ayman Mohamed AbdelWahed Mohamed; Ahmed Fathi Hassan Elkhouly; Abdelkarem Hussiny Ismail Elsayed; Zaky Ftouh Rashed; Ahmed Mohamed Abdelhakim; Mrooj Mabruk Almutairi; Mohamed A. Lotfy; et al. (Brazilian Journal of Anesthesiology)
Background: Peripheral abdominal nerve blocks are key components of multimodal analgesia, enhancing recovery after cesarean sections. This systematic review and meta-analysis aimed to assess analgesic efficacy of Erector Spinae Plane Block (ESPB) versus Transversus Abdominis Plane Block (TAPB) under ultrasound guidance following Cesarean Section (CS) under spinal anesthesia. Methods: A comprehensive search was conducted across PubMed, Scopus, Cochrane Library, and ISI Web of Science to identify relevant trials. The inclusion criteria followed the PICOS framework: Population (women undergoing elective cesarean delivery), Intervention (ESPB), Comparator (TAPB), Outcomes (postoperative pain, opioid consumption, analgesic duration, and satisfaction), and Study Design (randomized controlled trials). Results: Seven RCTs (380-patients) met the inclusion criteria. The ESPB group had significantly lower postoperative pain scores at rest and during movement, reduced 24-hour opioid consumption (MD = -2.62 MME; 95% CI -4.11 to -1.13; p = 0.006), and longer analgesic duration (SMD = 1.77; 95% CI 1.11 to 2.44; p < 0.001) than the TAPB group. Patient satisfaction was also significantly higher in the ESPB group (OR = 4.75; 95% CI 2.26 to 9.99; p < 0.001). While most outcomes demonstrated low heterogeneity, significant variability was observed in analgesic duration (I2 = 83%), requiring cautious interpretation. Conclusions: The ESP block offers superior pain relief, reduces opioid use, and enhances satisfaction compared to the TAP block in cesarean sections. These findings suggest that the implementation of the ESP block in postoperative analgesia protocols could significantly improve patient outcomes, potentially leading to enhanced recovery and reduced reliance on opioids.